Utilizing Positive Heutagogy on Learners Discipline: An Assessment - Orlanda, Mayette; Terones, Clariza; Zoleta, Marites (JPAIR Multidisciplinary Research, 2024)
Heutagogy, also known as self-determined learning, is a student-centered approach that emphasizes autonomy and capability development. In a heutagogical context, students actively explore areas of uncertainty within their topics. Teachers facilitate this process by providing background information and allowing students to delve deeply into subjects. This study explores the impact of the UPHOLD (Utilizing Positive Heutagogy on Learners’ Discipline) approach on the academic performance of Hearts and Hands Extended to Learners Progress (HELP) recipients for the academic year 2021-2022, using a descriptive-comparative method. The research focused on assessing changes in learners’ performance and the number of HELP recipients before and after the implementation of UPHOLD. The results indicated a significant improvement in performance for Grade 1 in Key Stage 1, while Grades 2 and 3 did not show the same improvement. In Key Stage 2, Grades 4, 5, and 6 all demonstrated noticeable improvement. Furthermore, there was a notable decrease in the number of HELP Program learners, suggesting that UPHOLD effectively promoted self-directed learning. However, it was observed that younger students in Grades 1 to 3, who struggle with independent learning, require more support. These findings highlight the importance of educators closely monitoring students’ learning independence to foster effective habits and prevent disengagement.